Emission reduction using biodiesel blends with nano-additives and reformed exhaust gas recirculation (REGR) in DI diesel engine. Issue 1 (31st December 2022) - Manieniyan, V.; Sukumar, V.; Senthilkumar, R.; Sivaprakasam, S.
Abstract : Internal combustion engines are important contributors to environmental and human health hazardous air pollution. This research work Reformed Exhaust Gas Recirculation (REGR) is very acutely focused on the viability of using B20MEOJAO (Methyl Ester of Jatropha with nano-additive of aluminium oxide) in diesel as a blend, and its performance, emission and combustion characteristics were evaluated. The energy balance analysis was carried in all the blends. As a result, the performance and emission were improved. The brake thermal efficiency is 3% higher in B20MEOJAO30ppm blend compared to REGR. The oxides of nitrogen emission reduced in 25% REGR B20MEOJAO30ppm blend compared to without REGR in diesel and B20MEOJAO30ppm. The lower NOx is lower in B20MEOJAO30ppm 20% REGR compared to diesel and other ratios. The B20MEOJAO30ppm blend energy utilisation is closer to diesel.